Attachment disorders diagnosed by community practitioners: a replication and extension. Issue 1 (27th June 2019) - Allen, Brian; Schuengel, Carlo
Abstract : Background: While considered a rare diagnosis, reactive attachment disorder (RAD) is simultaneously the subject of considerable debate. A recent report suggested that RAD is overdiagnosed in community settings and that conduct problems may be used to make a diagnosis of RAD (Woolgar & Baldock, Child and Adolescent Mental Health, 20, 2015, 34–40). This study seeks to replicate and extend these findings. Method: Clinical assessment data from 100 consecutive admissions of maltreated foster and adopted children (ages 3–17) to a specialty treatment clinic in the United States were reviewed. Measures included semi‐structured interviews of RAD and disinhibited social engagement disorder (DSED) symptoms and caregiver‐report questionnaires of emotional problems, conduct problems, and the quality of the parent–child relationship. Results: Of the 100 cases reviewed, 39 presented with a diagnostic history of RAD, DSED, or 'attachment disorder'. Of these cases, three were diagnosed in‐clinic with DSED; no cases met diagnostic criteria for RAD according to DSM‐5 criteria. However, analyses found that those diagnosed with RAD by community‐based clinicians were significantly more likely to display conduct problems and to be adopted (as opposed to in foster care). Conclusions: These findings confirm those of Woolgar and Baldock (Child and Adolescent Mental Health, 20, 2015, 34–40). It appears that the diagnostic criteria of RAD are commonly being inaccurately applied in general community‐based practice. Clarification of diagnostic criteria for RAD in recent revisions of diagnostic taxonomies, the accumulation of empirical data on RAD, and improved instrumentation are either poorly disseminated or inadequately implemented in community‐based practice settings. Abstract : Read the Commentary on this article at doi: 10.1111/camh.12357